Global distribution of groundwater‐vegetation spatial covariation - Koirala, Sujan; Jung, Martin; Reichstein, Markus; Graaf, Inge E. M.; Camps‐Valls, Gustau; Ichii, Kazuhito; Papale, Dario; Ráduly, Botond; Schwalm, Christopher R.; Tramontana, Gianluca; Carvalhais, Nuno (Geophysical research letters, 2017)
Groundwater is an integral component of the water cycle, and it also influences the carbon cycle by supplying moisture to ecosystems. However, the extent and determinants of groundwater‐vegetation interactions are poorly understood at the global scale. Using several high‐resolution data products, we show that the spatial patterns of ecosystem gross primary productivity and groundwater table depth are correlated during at least one season in more than two thirds of the global vegetated area. Positive relationships, i.e., larger productivity under shallower groundwater table, predominate in moisture‐limited dry to mesic conditions with herbaceous and shrub vegetation. Negative relationships, i.e., larger productivity under deeper groundwater, predominate in humid climates with forests, possibly indicating a drawdown of groundwater table due to substantial ecosystem water use. Interestingly, these opposite groundwater‐vegetation interactions are primarily associated with differences in vegetation than with climate and surface characteristics. These findings put forth the first evidence, and a need for better representation, of extensive and non‐negligible groundwater‐vegetation interactions at the global scale. Key Points Local‐scale groundwater‐vegetation spatial covariations are prevalent globally Both positive and negative relationships are equally widespread There is a stronger association of the sign of relationship with vegetation than with climate and land surface characteristics